2016
DOI: 10.1177/1550147716678426
|View full text |Cite
|
Sign up to set email alerts
|

A novel trajectory similarity–based approach for location prediction

Abstract: Location prediction impacts a wide range of research areas in mobile environment. The abundant mobility data, produced by mobile devices, make this research area attractive. Randomness makes people's future whereabouts hard to predict, although studies have proved that human mobility shows strong regularity. Most previous works, in general, tend to discover an association between a user's social relations in real world and variances in trajectory and then utilize this association to model the user's mobility w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The TLP algorithm works on the social mobility paradigm. The group of users are discovered having high trajectory similarity [ 20 ]. TLP is a multi-step process.…”
Section: Existing Trajectory Prediction Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TLP algorithm works on the social mobility paradigm. The group of users are discovered having high trajectory similarity [ 20 ]. TLP is a multi-step process.…”
Section: Existing Trajectory Prediction Algorithmsmentioning
confidence: 99%
“…A future location prediction method, i.e., Spatial-Temporal Recurrent Neural Networks (ST-RNN) was presented by [ 20 ]. The experimental results on real datasets showed that ST-RNN outperformed the futuristic methods and can model the spatial and temporal contexts.…”
Section: Related Workmentioning
confidence: 99%
“…Generally, location data have three forms. A "location" is actually a point of interest (POI) (e.g., checkin data [18,5,15,8,12,13,19,20,22,23]), a connected region (e.g., a region covered by a base station [10,11,2] or a surveillance camera [17,6], or a pair of coordinates (e.g., GPS coordinates [16,3,4,7,9,1,21]). For POI data, the location granularity is fully determined by the granularity of POIs.…”
Section: Location Granularitymentioning
confidence: 99%
“…The ability to predict the next location of a user is widely believed to be beneficial for many applications and services, including but not limited to smart transportation, personalized service recommendation, public resource management, and so on. Up to now, a large amount of mobility prediction methods have been proposed, ranging from pattern-based methods [1,2,3,4,5], to Markov model-based methods [6,7,8,9,10,11,12,13,14,15,16,17], and to deep neural networks [18,19,20,21]. These models are applied to various scenarios, including indoor walking [9], venue recommendation [15], urban commuting [19], or even intercontinental trips [18].…”
Section: Introductionmentioning
confidence: 99%